The Socio-Psychological Features of Working with Young People in the Corporate Governance System at the Russian Railways Company - Olga A. Kolosova, Tatiana A. Evstratova,Elena E. Kabanova, Ekaterina A. Vetrova, Olga A. Kulikova, (Opción, 1970)
Improving tools and methods for working with young people at Russian enterprises is poorly developed currently, but strategically important element of both short- and long-term planning of their activities, determines the competitive position of the enterprise, and creates conditions for its further development. The development of a corporate youth policy of an enterprise should be based on an assessment of the effectiveness of organizational and managerial tools and methods within a particular enterprise aimed at attracting, retaining and integrating young employees into the organizational environment. The company's youth policy is implemented in the legal framework of the state youth policy.